По Уссурийскому краю: Роман / В. К. Арсеньев - Арсеньев Владимир Клавдиевич (Кн. издательство, 1984)
Экземпляры: (20190522) / Инвентарный номер: 21113 / Сис.шифр: 26.89 / Авт.знак: А85 / ББК: 26.890(2Р55)